Embryonal rhabdomyosarcoma presenting as edema of the soft palate and necrosis of the uvula: a case report and review of the literature - Wengerman, Oscar Calderon; Epelstein, Jonathan Maya; De La Garza Hesles, Hector; Yaffe, Michelle Mizrahi; Sanabrais López, María J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Rhabdomyosarcoma (RMS) is a malignant tumor that affects skeletal muscles, typically found in the head and neck region of children. There have been a few reported cases of RMS occurring in the oral cavity. The prognosis of a patient with this condition depends on many clinical and biological factors, including age, the location of the tumor, histopathological subtype, and whether it has spread at the time of diagnosis. This case report and literature review focus on an unusual presentation of embryonal RMS in the uvula. The report described a case of a young Mexican child presented with symptoms such as edema, swelling of the soft palate, and necrosis of the uvula. The authors discuss the characteristics, management, and treatment of this neoplasm, providing valuable insights on the prognosis and therapeutic approaches for this rare condition and considering that the head and neck region can be a challenging site to treat due to the young age of the patient and the critical anatomy of this area.